PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Ervina Tjoandy; Devie Devie Devie (Business Accounting Review, 2018)
The prosperity of shareholders is optimally achieved through an increase in the value of the company. The aims of this study was to examine the direct influence of managerial ownership on dividend policy and firm value. In addition, this study also aimed to examine the indirect influence of the managerial ownership on firm value by using dividend policy as a mediating variable. The sample constituted of 41 manufacture companies listed in Indonesia Stock Exchange during the period of 2012- 2015. The data was collected from annual reports and then analyzed by using WarpPLS version 5.0 software.The statistical result stated that managerial ownership had positive significant influence on firm value, managerial ownership had positive significant influence on dividend policy and dividend policy had positive significant influence on firm value